2020
DOI: 10.1021/acs.jpcc.0c05716
|View full text |Cite
|
Sign up to set email alerts
|

On Self-Limiting Rotation and Diffusion Mechanisms during Sintering of Silver Nanowires

Abstract: Understanding the mechanisms and kinetics of thermal sintering between silver nanowires (NWs) is critical for multiple emerging applications. We use molecular dynamics simulations to reveal the kinetics and mechanisms of sintering between stacked silver NW pairs with nonparallel axes, which realistically mimics geometric configurations in experimentally relevant NW networks. Relative NW orientation has a hitherto-unknown but significant and nonlinear influence on inter-NW neck growth. This is due to a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…This model assumes that the change in ensemble resistivity during sintering is solely due to inter-NW neck growth. It also incorporates the following mechanistic insights from our past MD simulations of isothermal sintering between Ag NW pairs . First, the neck boundary is modeled as a 3D curve, as shown in Figure f.…”
Section: Modeling Approach and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This model assumes that the change in ensemble resistivity during sintering is solely due to inter-NW neck growth. It also incorporates the following mechanistic insights from our past MD simulations of isothermal sintering between Ag NW pairs . First, the neck boundary is modeled as a 3D curve, as shown in Figure f.…”
Section: Modeling Approach and Resultsmentioning
confidence: 99%
“…Second, because of NW rotation, the diffusion coefficients corresponding to neck growth and the virtual torque corresponding to NW rotation are functions of the NW radius R , instantaneous orientation angle θ, and the sintering temperature T . Readers are referred to this past work for further details of MD simulations …”
Section: Modeling Approach and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase-field modelling has been used previously to simulate the sintering of Ag nanoparticles [67]. The effect of local sintering at the junction of nanowires have also been studied using atomistic simulation methods, where it was observed that the nanowires undergo self-limiting rotation during neck growth, which is a result of complex interaction of surface diffusion and dislocation growth [68]. We also observe the nanowire junction break-up in all cases described above as a result of local sintering at the junctions of nanowires.…”
Section: Effect Of Relative Orientationmentioning
confidence: 99%